Mixed-member electoral systems the best of both worlds? - Shugart, Matthew Soberg 1960-.; Wattenberg, Martin P. 1956-. (Oxford Oxford University Press, 2001)
In the view of many electoral reformers, mixed-member systems offer the best of the traditional British single-seat system and PR systems. This book evaluates why the systems have appealed to many countries, and how well expectations have been met.
Keywords: Proportional representation; Comparative government